Effect of polysulfone brush functionalization on thermo-mechanical properties of melt extruded graphene/polysulfone nanocomposites. (October 2019) - Peña-Bahamonde, Janire; San-Miguel, Verónica; Baselga, Juan; Fernández-Blázquez, Juan P.; Gedler, Gabriel; Ozisik, Rahmi; Cabanelas, Juan C.
Abstract: The current work reports the preparation of nanocomposites of polysulfone (PSU) reinforced with reduced graphene oxide (rGO) by a solvent-free extrusion-injection method. In order to improve nanofiller dispersation, rGO was covalently grafted with PSU brushes via click chemistry. Several rGO/PSU nanocomposites with concentrations up to 3% (by weight) were prepared with both unmodified and PSU-grafted rGO. Morphology of the rGO/PSU nanocomposites were characterized via FE-SEM and TEM, which revealed a better dispersion state when rGO was grafted with PSU. Thermo-mechanical characterization of the rGO/PSU which improved the overall mechanical properties compared to unmodified rGO/PSU composites. An increase in the glass transition temperature ( T g ) of the PSU matrix was also observed. Nanocomposites did not reach complete rheological percolation, therefore, the results have been explained in terms of the entanglement of grafted and matrix PSU chains leading to improved interphase effects. The presence of grafted polymer chains also increased the sliding capacity favoring the sample deformation with subsequent toughness improvement. The proposed solvent-free extrusion-injection method is easily scalable and enables the potential uses of rGO/PSU nanocomposites. Graphical abstract: Image 1 Highlights: Nanocomposites of polysulfone with functionalized rGO with PSU brushes have been prepared. Nanoreinforced composites were prepared by a solvent-free extrusion-injection method. Grafting of PSU brushes to rGO favors dispersion in PSU matrix improving the interfacial interaction. An improved thermal and mechanical behavior compared to unmodified rGO/PSU nanocomposites was achieved.